JIHAD IN THE PERSPECTIVE OF AL-QURAN - Anirah, Andi; Nasbih, Ibrahim (Program Pascasarjana, UIN Alauddin Makassar, 2020)
The main problem that will be discussed in this wrinting is what is the concept of jihad in the Quran. The problem is discussed using tafsir approach by Maudhu’iy method. The result of this research shows that: a) Jihad is way of struggle to do anything we can do to achieve a specific goal, whether by spoken or real actions. It also means to spread the Islamic teachings and values. Jihad, as it is mentioned in Quran, does not only mean a way to face against the enemy, hardship, or struggle for it, but also an act to eradicate stupidity, poverty and illness, self-control, wisdom and patience to confront all the miserableness; b) Jihad consisted of kinds of jihad, form of jihad, and way to do jihad. Jihad has two kinds. First, fighting the enemies (kafir and munafiq). Second, fighting against the carnality and fighting against the musyrikin opression. There are two forms of jihad, a jihad in the name of Allah and jihad for Allah. Jihad can be committed by Quran, weapon, wealthiness, and life; and c) Jihad is crucial that remind us again of who we are before God, and to estabilish a civilization under the preferences of Allah. Jihad is a pathway to the order. And to do so, struggle is a must. In Quran, jihad will be rewarded jannah (heaven), given a good grade from Allah, and will be fortunate.